Arts-Based Interventions for Professionals in Caring Roles During and After Crisis: A Systematic Review of the Literature - Havsteen-Franklin, Dominik; Tjasink, Megan; Kottler, Jacqueline Winter; Grant, Claire; Kumari, Veena (Frontiers in Psychology, 2020)
Crisis events, such as the COVID-19 pandemic, can have a devastating effect on communities and the care professionals within them. Over recent years, arts-based interventions have helped in a wide range of crisis situations, being recommended to support the workforce during and after complex crisis but there has been no systematic review of the role of arts-based crisis interventions and whether there are cogent themes regarding practice elements and outcomes. We, therefore, conducted a systematic review to (i) define the arts-based change process used during and after crisis events, and (ii) explore the perceptions of intermediate and long-term mental health benefits of arts-based interventions for professionals in caring roles. Our search yielded six studies (all qualitative). All data were thematically aggregated and meta-synthesised, revealing seven practice elements (a safe place, focusing on strengths and protective factors, developing psychosocial competencies to support peers, emotional expression and processing, identifying and naming the impact of the crisis, using an integrative creative approach, and cultural and organisational sensitivity) applied across all six studies, as well as a range of intermediate and long-term benefits shared common features (adapting, growing and recovering; using the community as a healing resource; reducing or preventing symptoms of stress or trauma reactions, psychophysiological homeostasis). The ways in which these studies were designed independently from one another and yet used the same practice elements in their crisis interventions indicates that there is comparability about how and why the arts-based practice elements are being used and to what effect. Our findings provide a sound basis and meaningful parameters for future research incorporating quantitative and qualitative approaches to firmly establish the effectiveness of art-based interventions, and how arts can support cultural sensitivity, acceptability and indicated outcomes, particularly those relating to stress and trauma during or following a crisis.